2014
DOI: 10.5751/es-07082-190449
|View full text |Cite
|
Sign up to set email alerts
|

An integrated framework for sustainable development goals

Abstract: ABSTRACT. The United Nations (UN) Rio+20 summit committed nations to develop a set of universal sustainable development goals (SDGs) to build on the millennium development goals (MDGs) set to expire in 2015. Research now indicates that humanity's impact on Earth's life support system is so great that further global environmental change risks undermining long-term prosperity and poverty eradication goals. Socioeconomic development and global sustainability are often posed as being in conflict because of tradeof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
152
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(181 citation statements)
references
References 27 publications
1
152
0
8
Order By: Relevance
“…In other words, these trade-offs can manifest at the household, local, regional or global scale, and can have varying effects at household food security (Griggs et al 2014;Kanter et al 2016;Yillia 2016). For example, the production of different bioenergy crops related in Africa can have important implications for carbon stocks and as a result the global climate (e.g., Elshout et al 2015;Romeu-Dalmau et al 2016), affecting thus the overall agricultural system considering that climate change is a major risk for agriculture in the continent (Muller et al 2011;Rosenzweig et al 2014).…”
Section: The Role Of Education and Gender Equalitymentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, these trade-offs can manifest at the household, local, regional or global scale, and can have varying effects at household food security (Griggs et al 2014;Kanter et al 2016;Yillia 2016). For example, the production of different bioenergy crops related in Africa can have important implications for carbon stocks and as a result the global climate (e.g., Elshout et al 2015;Romeu-Dalmau et al 2016), affecting thus the overall agricultural system considering that climate change is a major risk for agriculture in the continent (Muller et al 2011;Rosenzweig et al 2014).…”
Section: The Role Of Education and Gender Equalitymentioning
confidence: 99%
“…However, there is a growing understanding that SDG2 is interlinked with several other SDGs related to poverty, gender equality, clean water and sanitation, climate change and biodiversity, among others (ICSU 2017). Several scholars have suggested that it is important to monitor and assess the synergies and tradeoffs among SDGs, especially at the local level (Griggs et al 2014;Kanter et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The SDG themselves have, on the one hand, re-emphasized the importance of research approaches, which enable an integrated perspective on global change and sustainability [1]. Such programs, like sustainability science, earth system analysis, human ecology or social ecology, have been around for quite some time now.…”
Section: Introductionmentioning
confidence: 99%
“…The definition, passage and implementation of the SDG can be interpreted as the attempt to initiate such social-ecological transformations. The prevailing critique of the SDG that they lack an integrative perspective and that, therefore, goal conflicts are likely [1,65,66], means, in our terminology: The interplay between the patterns and modes of regulation that the various SDG address were not sufficiently taken into account.…”
mentioning
confidence: 99%
“…The SDGs identify a range of economic, social, and environmental goals that are intended to form the basis for sustainable development. Like the Millennium Development Goals (MDGs) before them, the SDGs may galvanize global awareness, public pressure, political accountability, and align development finance to measurable targets and indicators (Poku and Whitman 2011;Sachs 2012;Ivanova 2013;Griggs et al 2014). Thus, they can function as a ''report card'' for countries to measure their sustainable development performance, now with greater attention to environmental issues than in the MDGs (Sachs 2012;Griggs et al 2014).…”
Section: Introductionmentioning
confidence: 99%